Correlation of clinical and radiographic severity of periodontitis with furcation involvement: Evaluation of periapical radiographs and Cone-beam Computed Tomography - Syurri Innaddinna Syahraini; Hanna Huzaima Bachtiar Iskandar; Bramma Kiswanjaya; Fatimah Maria Tadjoedin (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: To analyze the correlation of clinical and radiographic features in periodontitis with furcation involvement. Materials and Methods: Cross-sectional analytic study of 30 mandibular molars from 13 patients (8 males and 5 females), who had periodontitis with furcation involvement, with purposive sampling. Clinical, periapical and CBCT examination were then carried out . Assessment for clinical dan CBCT based on modified Glickman classification. Correlation test was performed with Kendall's Tau_b. Results: There was a significant difference between subjects of non CBCT group (clinical (p=0,01) and periapical (p=0,026)), with subjects examined by CBCT. However there was no difference between the clinical and periapical group. There is a correlation between furcation involvement on CBCT and periapical group (r=0,528; p=0,003). Conclusion: There was no correlation between furcation involvement on clinical examination with periapical radiographs and CBCT. The correlation is only seen between periapical radiographs and CBCT.